Use of buffered hypochlorite solution for disinfecting fibrescopes. Issue 3 (March 1982) - Coates, D; Death, J E
Abstract : The possible use of sodium hypochlorite solution buffered to pH 7.6 and containing 100 ppm available chlorine (avCl) for disinfecting fibrescopes was investigated. A flexible fibrescope experimentally contaminated with Pseudomonas putida, Mycobacterium fortuitum, or Bacillus subtilis spores was effectively disinfected within 10 m in repeatedly and without any observable adverse effect on the instrument. The corrosive nature of buffered hypochlorite was investigated by immersing various fibrescope components and metal wires in solutions of different strength for long periods and examining them for damage. Stainless steel, platinum, glass, Teflon, polythene and epoxy resin were apparently unaffected whereas polyurethane, rubber and other metals tested were damaged to different extents. Buffered hypochlorite solutions may have many applications pertaining to the disinfection of items which are either thermolabile or require rapid effective disinfection.